Uncovering Symbionts Across the Psyllid Tree of Life and the Discovery of a New Liberibacter Species, “Candidatus” Liberibacter capsica - Kwak, Younghwan; Sun, Penglin; Meduri, Venkata RamaSravani; Percy, Diana M.; Mauck, Kerry E.; Hansen, Allison K. (Frontiers in Microbiology, 2021)
Sap-feeding insects in the order Hemiptera associate with obligate endosymbionts that are required for survival and facultative endosymbionts that can potentially modify resistance to stress, enemies, development, and reproduction. In the superfamily Psylloidea, the jumping plant lice (psyllids), less is known about the diversity and prevalence of their endosymbionts compared to other sap-feeding pests such as aphids (Aphididae). To address this knowledge gap, using 16S rRNA sequencing we identify symbionts across divergent psyllid host lineages from around the world. Taking advantage of a new comprehensive phylogenomic analyses of Psylloidea, we included psyllid samples from 44 species of 35 genera of 5 families, collected from 11 international locations for this study. Across psyllid lineages, a total of 91 OTUs were recovered, predominantly of the Enterobacteriaceae (68%). The diversity of endosymbionts harbored by each psyllid species was low with an average of approximately 3 OTUs. Two clades of endosymbionts (clade 1 and 2), belonging to Enterobacteriaceae, were identified that appear to be long term endosymbionts of the psyllid families Triozidae and Psyllidae, respectively. We also conducted high throughput metagenomic sequencing on three Ca. Liberibacter infected psyllid species (Russeliana capsici, Trichochermes walkeri, and Macrohomotoma gladiata), initially identified from 16S rRNA sequencing, to obtain more genomic information on these putative Liberibacter plant pathogens. The phylogenomic analyses from these data identified a new Ca. Liberibacter species, Candidatus Liberibacter capsica, that is a potential pathogen of solanaceous crops. This new species shares a distant ancestor with Ca. L. americanus, which occurs in the same range as R. capsici in South America. We also detected the first association between a psyllid specializing on woody hosts and the Liberibacter species Ca. L. psyllaurous, which is a globally distributed pathogen of herbaceous crop hosts in the Solanaceae. Finally, we detected a potential association between a psyllid pest of figs (M. gladiata) and a Ca. Liberibacter related to Ca. L. asiaticus, which causes severe disease in citrus. Our findings reveal a wider diversity of associations between facultative symbionts and psyllids than previously reported and suggest numerous avenues for future work to clarify novel associations of ecological, evolutionary, and pathogenic interest.